Determinants of Capital Structure and the Effect on Financial Performance: Testing Pecking Order and Trade-Off Models - Sufitrayati; Nursaimatussaddiya (Jurnal Ilmiah Manajemen Kesatuan, 2026)
This study investigates the determinants of capital structure and their implications for the financial performance of corporate firms operating by integrating the Pecking Order Theory and Trade-Off Theory. Using a sample of firms with complete and publicly available financial reports from 2020 to 2024, this research examines the influence of profitability, liquidity, firm size, asset structure, and firm growth on capital structure decisions, as well as the mediating effect of capital structure on financial performance. The study employs panel data regression with comprehensive diagnostic testing, including normality, multicollinearity, heteroscedasticity, and autocorrelation assessments to ensure the validity and reliability of the model. The results reveal that profitability and liquidity negatively affect leverage, supporting the pecking order theory, while firm size and asset structure positively influence debt levels, consistent with the trade-off theory. Capital structure is further found to play a significant role in strengthening financial performance, indicating that optimal leverage can enhance corporate value. This study contributes to the literature by providing empirical evidence from a developing regional context and by combining two dominant theoretical perspectives to explain capital structure behavior.